1996
DOI: 10.1536/ihj.37.317
|View full text |Cite
|
Sign up to set email alerts
|

Significant Characteristics of Variant Angina Patients with Associated Syncope.

Abstract: To determine whether syncope predisposes to sudden cardiac death, variant angina patients with syncope during cardiac attacks were compared with those without syncope. There were 240 consecutive patients (193 males and 47 females) diagnosed with variant angina pectoris. Thirty patients had a history of syncope during cardiac attacks while the remaining 210 had none. The incidence of cardiac events in the former group was 10.0% (3 of 30) and 10.5% in the latter. There were 3 cases of sudden cardiac death, all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Although the most common cause of ST elevations (STE) in the perioperative setting is acute coronary syndrome (ACS), alternative diagnoses should be considered to ensure the patient does not undergo unnecessary and invasive investigations [4]. ST-changes in coronary vasospasm usually last less than 15 minutes, with the electrocardiogram (ECG) spontaneously returning to baseline [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the most common cause of ST elevations (STE) in the perioperative setting is acute coronary syndrome (ACS), alternative diagnoses should be considered to ensure the patient does not undergo unnecessary and invasive investigations [4]. ST-changes in coronary vasospasm usually last less than 15 minutes, with the electrocardiogram (ECG) spontaneously returning to baseline [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with VA show ST segment elevation and reciprocal depression on ECG during attacks of chest pain. Ambulatory ECG monitoring in patients with VA showed circadian variation with most of the ischemic episodes occurring between midnight to early morning hours with peak frequency around 05.00 h [6]. Another important feature of VA is the frequency of asymptomatic ischemic episodes being much higher than symptomatic episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Another important feature of VA is the frequency of asymptomatic ischemic episodes being much higher than symptomatic episodes. One study revealed that 82% (872 out of 1062) of episodes were asymptomatic [6]. Severe arrhythmias, including ventricular tachycardia, highdegree atrioventricular block, and bradyarrythmias resulting in syncopal episodes may be occasionally seen during an attack of VA.…”
Section: Discussionmentioning
confidence: 99%
“…These syncopes have been associated with severe cardiac arrhythmias such as ventricular tachycardia or fibrillation, bradyarrhythmias, as well as atrioventricular block [17].…”
Section: Review Of Literature and Commentmentioning
confidence: 99%